2003
DOI: 10.1007/978-3-540-40968-7_19
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence and Quantum-State Measurement in Quantum Optics

Luiz Davidovich

Abstract: Abstract. This paper discusses work developed in recent years, in the domain of quantum optics, which has led to a better understanding of the classical limit of quantum mechanics. New techniques have been proposed, and experimentally demonstrated, for characterizing and monitoring in real time the quantum state of an electromagnetic field in a cavity. They allow the investigation of the dynamics of the decoherence process by which a quantum-mechanical superposition of coherent states of the field becomes a st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…16, was introduced as a potential operation by Davidovich and co-workers [19,20], who called it a quantum switch, because a qubit coherently switches a classical driving field on a mode. These papers suggested that a quantum switch might be realized at microwave frequencies in a qubit/cavity set-up like that in Serge Haroche's Paris laboratory [23,24]: a rubidium atom occupying one of two Rydberg levels, which constitute the qubit, passes through a superconducting microwave cavity; one level does not interact with the microwave field, but the other dispersively switches a cavity mode into resonance with a classical driving field, which excites the mode into a coherent state.…”
Section: Coherent-state-superposition Interferometersmentioning
confidence: 99%
See 1 more Smart Citation
“…16, was introduced as a potential operation by Davidovich and co-workers [19,20], who called it a quantum switch, because a qubit coherently switches a classical driving field on a mode. These papers suggested that a quantum switch might be realized at microwave frequencies in a qubit/cavity set-up like that in Serge Haroche's Paris laboratory [23,24]: a rubidium atom occupying one of two Rydberg levels, which constitute the qubit, passes through a superconducting microwave cavity; one level does not interact with the microwave field, but the other dispersively switches a cavity mode into resonance with a classical driving field, which excites the mode into a coherent state.…”
Section: Coherent-state-superposition Interferometersmentioning
confidence: 99%
“…In its translations from atoms to photons, this paper formulates a quantum-circuit version of the equivalence between atomic and optical interferometry demonstrated by Yurke, McCall, and Klauder [16]. Much of the paper's content on phase estimation and interferometry is anticipated by the work of Gerry and collaborators [5,7,9,10,17], and many of the qubit-mode operations discussed in the paper follow a path blazed by Davidovich, Haroche, and collaborators [18,19,20,21,22,23,24]. Lee, Kok, and Dowling [8] made an initial foray into the domain of quantum circuits as tools for investigating equivalent atomic and optical interferometers, calling this the "quantum Rosetta stone."…”
Section: Introductionmentioning
confidence: 99%